2016
DOI: 10.1108/md-01-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Using transaction cost economics to explain open innovation in start-ups

Abstract: Purpose The basic concept of transaction cost theory is that firms like to conduct transactions in a channel with lower transaction costs. Therefore, the purpose of this paper is to use the transaction cost perspective to identify which conditions cause companies to choose between outbound open innovation (hierarchy governance) and inbound open innovation (market governance). Design/methodology/approach Accordingly, transaction cost economics was used to relate the choice and implementation of open innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 79 publications
1
19
0
3
Order By: Relevance
“…With reference to the transaction cost theory, Hsieh et al (2016) identified which circumstances must be predominant for young ventures to move towards either inbound or outbound OI. Hsieh et al found that when both asset specificity, as well as behavioural uncertainty, were high, young ventures tended to increase their outbound OI practices.…”
Section: Selection Of Inbound Vs Outbound Oimentioning
confidence: 99%
“…With reference to the transaction cost theory, Hsieh et al (2016) identified which circumstances must be predominant for young ventures to move towards either inbound or outbound OI. Hsieh et al found that when both asset specificity, as well as behavioural uncertainty, were high, young ventures tended to increase their outbound OI practices.…”
Section: Selection Of Inbound Vs Outbound Oimentioning
confidence: 99%
“…Out of these other actors, Universities, large companies and venture capital (VC) firms are highlighted. It is worth noting the transdisciplinarity of OI research, as some papers focus on with financing (Livieratos and Lepeniotis 2017), intellectual property (Belingheri and Leone 2017), transaction costs (Hsieh et al 2016), and alliances (Jackson and Richter 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to it, specific dimensions of OI are inward intellectual propoerty licensing and external participation, outsourcing R&D and external networking, customer involvement, employee involvement, venturing and outward intellectual property licensing. Hsieh et al (2016) defined the key factors that influence start-ups' OI activities as dedicated asset specificity, human asset specificity, environmental uncertainty, behavioral uncertainty, transaction frequency and number of parties. Lopes and de Carvalho (2018) identified the OI antecedents in two groups as openness (business model, human aspects, innovativeness, number of partners, strategy) and main players (competitors, consultants, customers, government, network partners, suppliers, universities and research institutes).…”
Section: Determininig the Criteriamentioning
confidence: 99%
“…Casprini et al (2017) purposed to clarify on how family firms execute OI strategies by directing knowledge flows with an exploratory case study on an Italian family firm. Hsieh et al (2016) identified which conditions cause firms to select between outbound and inbound OI.…”
Section: Introductionmentioning
confidence: 99%